2000
DOI: 10.1007/s002470050026
|View full text |Cite
|
Sign up to set email alerts
|

Not all rods are Harrington - An overview of spinal instrumentation in scoliosis treatment

Abstract: An overview of spinal instrumentation in scoliosis treatment will allow better understanding of the purposes of the hardware and how it relates to the spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…4,34 Although some authors have reported good results after nonfusion-related decompression, the emerging consensus is that decompression and posterolateral fusion offer the best clinical results (Fig. Lateral recess decompression is conducted, when necessary, by undercutting of the facet joints.…”
Section: Spinal Stenosis and Spondylolisthesismentioning
confidence: 99%
“…4,34 Although some authors have reported good results after nonfusion-related decompression, the emerging consensus is that decompression and posterolateral fusion offer the best clinical results (Fig. Lateral recess decompression is conducted, when necessary, by undercutting of the facet joints.…”
Section: Spinal Stenosis and Spondylolisthesismentioning
confidence: 99%
“…Currently, there are many different implants available for the treatment of scoliosis. Implant systems differ depending upon patient indications [4].…”
Section: Introductionmentioning
confidence: 99%
“…And later on surgical conservation gained popularity, especially by Harrington's invention of correction by intra-operatively expandable metal rods. An explosion in variety of implants followed [6]. But no imminent concept of the working mechanism of the still existent black box is formulated or tested: an explanation concerning how growth is organized and regulated (forces, masses, volumes) by the oldest organ of animal life: the central nervous system in vertebrates.…”
Section: Introductionmentioning
confidence: 99%